2009
DOI: 10.1103/physrevc.80.064901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bulk viscosity on elliptic flow near the QCD phase transition

Abstract: In this work, we examine the effect of bulk viscosity on elliptic flow, taking into account the critical behavior of the equation of state and transport coefficients near the QCD phase transition. We found that the p T dependence of v 2 is quantitatively changed by the presence of the QCD phase transition. Within reasonable values of the transport coefficients, v 2 decreases by a factor of 15% at small p T values (<1 GeV). However, for larger values of p T (>2 GeV), the interplay between the velocity of sound … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
123
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(124 citation statements)
references
References 48 publications
0
123
0
1
Order By: Relevance
“…These momentum distribution of Γ π and Γ N will be integrated out when we will estimate ζ π and ζ N from Eqs. (8) and (9) respectively. Let us come to the different loop contributions of pion and nucleon thermal width in bulk viscosity coefficient of hadronic matter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These momentum distribution of Γ π and Γ N will be integrated out when we will estimate ζ π and ζ N from Eqs. (8) and (9) respectively. Let us come to the different loop contributions of pion and nucleon thermal width in bulk viscosity coefficient of hadronic matter.…”
Section: Resultsmentioning
confidence: 99%
“…[5] exposes the possibility of divergence of ζ near the transition temperature. In recent times, different phenomenological investigations [6][7][8][9][10][11][12][13][14][15][16][17][18] demonstrated that bulk viscosity can have a non-negligible effect on heavy ion observables, where the values of ζ/s in Ref. [18] is assumed to be quite large.…”
Section: Introductionmentioning
confidence: 99%
“…See also Refs. [90][91][92][93] for recent work on the reliability of Grad's ansatz. By performing viscous hydrodynamic simulations with different dependencies of δf on p T , the authors of Refs.…”
Section: -5mentioning
confidence: 99%
“…Before discussing how the quark polarization evolves in a viscous QGP due to multiple scattering, we have to know how the QGP itself evolves through either transport model or viscous hydrodynamical model [9,10,[27][28][29][30][31], Moreover, we also have to know the initial profile of the longitudinal flow field. In the discussion in Sec.…”
Section: Relativistic Laminar Flowmentioning
confidence: 99%